Potencial anticâncer do óleo essencial das folhas de Lippia gracilis Schauer (Verbenaceae) - Ferraz, Rosana Paula Cruz (2013)
Medicinal plants are one of the most important sources of drugs used in the pharmaceutical industry. Among traditional medicinal plants of the Brazilian northeastern, Lippia gracilis Schauer (Verbenaceae) had been used for several medicinal purposes. Therefore, the present study aimed to determine the chemical composition of the leaf essential oil (EO) of L. gracilis, as such to evaluate it in vitro and in vivo anticancer potential. For that, the leaf essential oil (EO) of L. gracilis was prepared using hydrodistillation followed by GC MS analysis. The cytotoxic effects of EO and its components (thymol, p-cymene, γ-terpinene and myrcene) have been assessed in HepG2, K562 and B16-F10 tumor cells as such in non- tumoral (PBMC). The effects of EO on cell proliferation and apoptosis induction were investigated in HepG2 cells. Furthermore, mice bearing Sarcoma 180 tumor cells were used to confirm its in vivo effectiveness. The results showed that the EO composition was characterized by the presence of thymol as major constituent which exhibited promising cytotoxicity against the all tumor cells tested, whereas its investigated components presented low cytotoxic potential. Moreover, EO treatment caused G1 arrest in HepG2 cells accompanied by the induction of DNA fragmentation without affecting cell membrane integrity. Cell morphology consistent with apoptosis and a remarkable activation of caspase-3 were also observed, suggesting induction of caspase-dependent apoptotic cell death. In vivo antitumor study showed tumor growth inhibition rates of 38.5 41.9%. In conclusion, the EO, which has thymol as its major constituent, possesses significant in vitro and in vivo antitumor activity. These data suggest that leaf essential oil of L. gracilis is a potential medicinal resource, which may ultimately be used in cancer treatment.